Cutaneous Lesions of Multiple Myeloma of the Lower Extremity Masquerading as Squamous Cell Carcinoma - Clutter, Courtney A (Cureus, 2020)
Cutaneous involvement in multiple myeloma (MM) is a rare manifestation, being more prevalent in patients with aggressive subtypes, and refractory to standard therapies. Due to the rarity of this diagnosis, the reported clinical characteristics have been protean and relatively non-specific. Lower extremity involvement of cutaneous MM is an uncommon anatomical location for this diagnosis. We present a patient with refractory IgG lambda MM, and a past medical history of squamous cell carcinoma of the lower extremities who developed cutaneous MM in his lower leg. At the time of initial evaluation, the lesions mimicked squamous cell carcinoma, posing a diagnostic challenge. Histopathological and immunohistochemical studies confirmed cutaneous involvement by multiple myeloma. There needs to be a high clinical suspicion for cutaneous MM in patients with MM presenting with new skin lesions.